DYNAMICS OF SWEET BASIL (Ocimum basilicum L.) GROWTH AFFECTED BY CULTIVAR AND FOLIAR FEEDING WITH NITROGEN - Renata Nurzyńska-Wierdak; Bartłomiej Borowski (Acta Scientiarum Polonorum: Hortorum Cultus, 2011)
Growing herbal plants is connected with obtaining the high yield of raw material, abundant in active substances. The growth and yield of these plants can be effectively improved by growing valuable cultivars and appropriate agrotechnical procedures. One of the latter is foliar feeding of plants with nitrogen, which is a fast-acting and extremely effective procedure. The conducted studies were aimed at comparing growth dynamics in four basil cultivars, including the Polish ones: Kasia and Wala, as well as determining the effect of foliar plant feeding with nitrogen upon their growth and development. The plants were grown from March till July 2008 and 2009 in an unheated foil tunnel. During the experiment the thermal conditions were generally favorable for basil development. Foliar feeding of basil was conducted with the use of hand spraying machine, dosing 0.5% urea solution. The examined basil cultivars were characterized by various growth dynamics, which was also related to temperature distribution in the growing period. The highest accretion was that of the Polish cultivar Kasia plants. The examined basil plants responded well to foliar nitrogen feeding. The application of urea contributed to a significant increase of the height of basil plants, as well as of the length and width of their leaf blades. However, this procedure did not simultaneously affect the plant diameter and number of sprout branchings.